ChemInform Abstract: Organocatalytic Multicomponent Reaction for the Acquisition of a Selective Inhibitor of mPTPB, a Virulence Factor of Tuberculosis. Issue 25 (3rd June 2013) - He, Rongjun; Zeng, Li‐Fan; He, Yantao; Wu, Li; Gunawan, Andrea Michelle; Zhang, Zhong‐Yin
Abstract Pyrrole‐based libraries (VII) of potent protein tyrosine phosphatase inhibitors with improved potency and selectivity are synthesized via an organocatalyzed multicomponent Mannich‐type reaction.